Biomechanical contribution of the alar ligaments to upper cervical stability. (23rd January 2020) - Tisherman, Robert; Hartman, Robert; Hariharan, Kharthik; Vaudreuil, Nicholas; Sowa, Gwendolyn; Schneider, Michael; Timko, Michael; Bell, Kevin
Abstract: Acute and chronic whiplash-associated disorders pose a significant healthcare burden due to chronic pain, which is associated with upper cervical instability resulting from ligamentous injury. No standard measure exists for diagnosing alar ligament injury and imaging findings vary widely. Multiple physical examination maneuvers are used to diagnose alar ligament injury including the C2 Spinous Kick, Flexion-Rotation, and Bending-Rotation tests. The objective of the current study was to determine the mechanical contribution of the alar ligaments to upper cervical stability and quantify the biomechanical changes seen during simulated clinical examinations after alar ligament injury. Eight cadaveric C0-C3 specimens were evaluated using a robotic testing system. Range of motion and moment at the end of intact specimen replay were the primary outcomes. Clinical examinations were simulated by rotation through two axes as performed during physical examination. Intact, unilateral and bilateral alar ligament injury states were tested. Unilateral alar ligament injury led to significant increases in lateral bending (12.0 ± 7.2%, p < 0.05), axial rotation (4.1 ± 2.4%, p < 0.05), and flexion-extension (5.3 ± 4.3%, p < 0.05) compared with intact specimens. The alar ligaments also contributed to resistance to intact motion in extension (13.4 ± 6.6%, p < 0.05), flexion (4.4 ± 2.2%, p < 0.05), axial rotation (19.3 ± 2.7%, p < 0.05), and lateral bending (16.0 ± 2.8%, p < 0.05). The C2 Spinous Kick Test showed the largest percentage change (−23.0 ± 14.8%), and the Bending-Rotation Test towards the side of injury significantly increased axial rotation by the largest absolute magnitude (5.5° ± 5.1°). Overall, quantifiable changes to motion measured during simulated physical examinations were found, but the ability of a clinician to feel these changes remains unknown.